2018
DOI: 10.1111/jocd.12787
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study comparing the efficacy of two formulations of botulinum toxin type A for muscular calves contouring

Abstract: This study demonstrated that PRA and ONA provided comparable efficacy and safety in gastrocnemius muscle reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…23 By utilizing the only state-of-the-art manufacturing process that employs a 2-step chromatographic purification process to extract from the complexing proteins and leave just the active 150kDa molecule, INCO provides the lowest protein load available compared to other BoNT/A formulations. 1,[24][25][26][27][28][29] INCO contains 0.44ng 150kDa neurotoxin per 100U (0.088 ng/20U dose) and has a high specific activity of 227U/ng, consistent with no denaturing of the BoNT complex during the INCO chromatographic purification process. [24][25][26][27][28][29] In contrast, ONA, ABO, and PRA all contain complexing proteins and/or denatured BoNT protein that may initiate an immune response, leading to production of neutralizing antibodies that can be associated with decreased effect over time or treatment non-response.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…23 By utilizing the only state-of-the-art manufacturing process that employs a 2-step chromatographic purification process to extract from the complexing proteins and leave just the active 150kDa molecule, INCO provides the lowest protein load available compared to other BoNT/A formulations. 1,[24][25][26][27][28][29] INCO contains 0.44ng 150kDa neurotoxin per 100U (0.088 ng/20U dose) and has a high specific activity of 227U/ng, consistent with no denaturing of the BoNT complex during the INCO chromatographic purification process. [24][25][26][27][28][29] In contrast, ONA, ABO, and PRA all contain complexing proteins and/or denatured BoNT protein that may initiate an immune response, leading to production of neutralizing antibodies that can be associated with decreased effect over time or treatment non-response.…”
Section: Safetymentioning
confidence: 99%
“…1,[24][25][26][27][28][29] INCO contains 0.44ng 150kDa neurotoxin per 100U (0.088 ng/20U dose) and has a high specific activity of 227U/ng, consistent with no denaturing of the BoNT complex during the INCO chromatographic purification process. [24][25][26][27][28][29] In contrast, ONA, ABO, and PRA all contain complexing proteins and/or denatured BoNT protein that may initiate an immune response, leading to production of neutralizing antibodies that can be associated with decreased effect over time or treatment non-response. 24,31 Investigational drug DaxibotulinumtoxinA (DAXI; RT002, Revance Therapeutics Inc.) contains a virally-derived protein transduction domain (PTD), as part of an added excipient and stabilizer (RTP004).…”
Section: Safetymentioning
confidence: 99%
“…Patients came in for follow‐ups visits at 1 and 6 months and were evaluated with clinical photography, calf‐circumference measurement, isokinetic analysis, and ultrasonographic imaging. Both patients' satisfaction rate and doctor's evaluation showed no statistical difference between the two formulations and thus the study showed that PRA and ONA provide comparable efficacy in calf reductions in hypertrophic gastrocnemius muscles 48 …”
Section: Resultsmentioning
confidence: 72%
“…Both patients' satisfaction rate and doctor's evaluation showed no statistical difference between the two formulations and thus the study showed that PRA and ONA provide comparable efficacy in calf reductions in hypertrophic gastrocnemius muscles. 48…”
Section: Calf Contouringmentioning
confidence: 99%
“…Growing demand for safer and less painful procedures for achieving slim body contour has led to the development of several noninvasive modalities including botulinum toxin type A (BTX-A). [1][2][3][4][5][6] To the best of our knowledge, no clinical study has been conducted to assess the aesthetic effect of BTX-A on deltoid muscle hypertrophy. Therefore, we conducted a pilot study to determine the efficacy and safety of intramuscular BTX-A injection in reducing deltoid muscle hypertrophy in Asian women.…”
Section: Introductionmentioning
confidence: 99%